2014
DOI: 10.1016/j.conb.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Dual-transmitter neurons: functional implications of co-release and co-transmission

Abstract: Co-transmission, the ability of a neuron to release multiple transmitters, has long been recognized in selected circuits. However, the release of multiple primary neurotransmitters from a single neuron is only beginning to be appreciated. Here we consider recent examples of co-transmission as well as co-release – the packaging of multiple neurotransmitters into a single vesicle. The properties associated with each mode of release greatly enhance the possible action of such neurons within circuits. The function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
141
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(144 citation statements)
references
References 89 publications
3
141
0
Order By: Relevance
“…Co-transmission of neurotransmitters has received increasing attention recently (Seal and Edwards 2006;Vaaga et al 2014). Glutamate is the main excitatory neurotransmitter at neuromuscular junctions in Drosophila (Jan and Jan 1976) and both immunocytochemical and electrophysiological studies have demonstrated that glutamate may also be released at peripheral synapses in the spider nervous system (Fabian-Fine et al 1999b;Panek and Torkkeli 2005).…”
Section: Anti-vesicular Gaba Transporter Immunolabelingmentioning
confidence: 99%
“…Co-transmission of neurotransmitters has received increasing attention recently (Seal and Edwards 2006;Vaaga et al 2014). Glutamate is the main excitatory neurotransmitter at neuromuscular junctions in Drosophila (Jan and Jan 1976) and both immunocytochemical and electrophysiological studies have demonstrated that glutamate may also be released at peripheral synapses in the spider nervous system (Fabian-Fine et al 1999b;Panek and Torkkeli 2005).…”
Section: Anti-vesicular Gaba Transporter Immunolabelingmentioning
confidence: 99%
“…Neurons signal using more than one chemical transmission mechanism, including co-transmission of different classes of neurotransmitter from distinct vesicles or co-release from the same vesicle [178][179][180][181][182][183]. This has long been recognized [181,184], but modern techniques provide excellent tools to detect co-transmission/release while mapping it onto defined neurons.…”
Section: Questions Limitations and Future Directionsmentioning
confidence: 99%
“…The ability to optogenetically activate genetically-defined cell types has led to a growing appreciation that mammalian neurons can release multiple fast-acting neurotransmitters (Hnasko and Edwards, 2012; Vaaga et al, 2014), subverting the classic notion that neuron classes can be defined by their ability to package and release a single primary neurotransmitter. Examples include spinal interneurons that release GABA and glycine (Jonas et al, 1998), midbrain dopaminergic neurons that also release glutamate and/or GABA (Stuber et al, 2010; Tecuapetla et al, 2010; Tritsch et al, 2012, 2014), and habenula-projecting neurons that release both GABA and glutamate (Root et al, 2014; Shabel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%